2010
DOI: 10.1002/cncr.25489
|View full text |Cite
|
Sign up to set email alerts
|

L‐asparaginase treatment in acute lymphoblastic leukemia

Abstract: Asparaginases are a cornerstone of treatment protocols for acute lymphoblastic leukemia (ALL) and are used for remission induction and intensification treatment in all pediatric regimens and in the majority of adult treatment protocols. Extensive clinical data have shown that intensive asparaginase treatment improves clinical outcomes in childhood ALL. Three asparaginase preparations are available: the native asparaginase derived from Escherichia coli (E. coli asparaginase), a pegylated form of this enzyme (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
452
0
29

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(483 citation statements)
references
References 130 publications
2
452
0
29
Order By: Relevance
“…Treatment with LAse, polyphenoloxidase and low frequency laser decreased adhesion of uropathogenic Escherichia coli to human erythrocytes [4] . LAse also known commercially as Oncaspar, Colaspase, Crasnitin, Kidrolase, Erwinase and Elspar [5] . It is also used in food industry for the production of acrylamide (a potent carcinogen and a neurotoxic compound) free starchy fry food [6] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with LAse, polyphenoloxidase and low frequency laser decreased adhesion of uropathogenic Escherichia coli to human erythrocytes [4] . LAse also known commercially as Oncaspar, Colaspase, Crasnitin, Kidrolase, Erwinase and Elspar [5] . It is also used in food industry for the production of acrylamide (a potent carcinogen and a neurotoxic compound) free starchy fry food [6] .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the morphological, biochemical and physiological tests were put into Bergey's Manual of Determinative Bacteriology [19] and bacterial identification software's like PIBwin version 2.0 and ABIS online for accurate identification. The isolate TPS-12 was exposed to temperature range of 40-100°C, pH range of [3][4][5][6][7][8][9][10][11][12] and sodium chloride concentrations range of 2%-10% for evaluation of physiological characteristics. The antibiogram pattern of the isolate TPS-12 was tested for sensitivity against different antibiotic discs (Himedia, Mumbai) viz., erythromycin (15 …”
Section: Identification Of the Bacterial Isolate Of Tps-12mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon administration, this drug converts serum asparagine into aspartate, thereby effectively depleting the blood from this amino acid. Unlike most other cells in the body, lymphocytes, including leukemic blasts, are fully dependent on uptake of asparagine from the blood and die as a result of nutrient stress (1).…”
mentioning
confidence: 99%
“…using dexamethasone instead of prednisolone, 7 and less so by the introduction of novel agents. More recently, therapy optimization focusses on asparaginase, including asparaginase dose intensification, therapeutic drug monitoring, and the use of novel pegylated formulations, as reviewed by Pieters et al 8 The progress made with these changes are not yet visible in the results reported by Gatta et al as these developments are too recent. At least as important are the improvements in supportive care reducing the number of patients dying from treatment-related mortality, 9 including developments in blood-banking, antibiotics and antifungals, parenteral nutrition and tumor lysis prevention.…”
mentioning
confidence: 99%